Age heaping patterns in Mosaic data. Issue 1 (2nd January 2018) - Szołtysek, Mikołaj; Poniat, R.; Gruber, S.
ABSTRACT: This paper analyzes the extent and nature of age-misreporting in the Mosaic data, currently one of the largest historical census microdata infrastructures for continental Europe. We use demographic measures known as the age heaping indexes to explore regional, periodic and sex-specific patterns of age misreporting across 115 Mosaic regional datafiles, from Catalonia to Moscow, during Europe's demographic ancien régime and thereafter. The paper's second significant contribution is the comparison of Mosaic-based results to those derived from two other big census data projects—IPUMS and NAPP. Beyond this exploratory data analysis, we also investigate possible sources of variation in age heaping across Mosaic data by examining how it relates to variability in socioeconomic, institutional, and environmental conditions. Overall, our systematic inquiry into quality of age reporting in Mosaic consolidates the project's potentially transformative role in comparative historical family demography and suggests some avenues for future research.